The Effect of Mobile Shopping Service Quality on Customer Satisfaction and Customer Loyalty: A Case of Bukalapak in Indonesia - Fadhilah Rahadatul Aisy; Adhi Prasetio (Shirkah: Journal of Economics and Business, 2024)
Bukalapak's position as the fifth-ranked e-commerce platform suggests a decrease in the number of visitors, which may be attributed to factors such as customer satisfaction. To address this, it is crucial to focus on mobile shopping service quality, customer satisfaction, and customer loyalty to retain and attract more users. This study aims to examine the effect of mobile shopping service quality on customer satisfaction and loyalty among Bukalapak users in Indonesia. The research employed a quantitative approach, utilizing a causal research design. Data was collected through questionnaires distributed to at least 400 respondents who have used or are currently using the Bukalapak. The data was analyzed using Structural Equation Modeling (SEM) in SPSS 29 as well as the AMOS 26 program. The analysis reveals that mobile shopping service quality has a significant and positive effect on customer satisfaction. Furthermore, customer satisfaction significantly affects customer loyalty. However, the effect of mobile shopping service quality on customer loyalty is positive but not significant. Factors such as efficiency, fulfillment, responsiveness, and contact demonstrate a significant and positive relationship with both customer satisfaction and loyalty.